Language use by tertiary students: The case of the National University of Lesotho - Dr. ’Maboleba Kolobe; Dr. ’Madira Thetso (Center of Language and Cultural Studies, 2019)
This study interrogates the use of language by students at tertiary. It focuses on students’ interactions with one another outside classroom setting. The study hypothesizes that the language used by university students display richness and yet complexity of human language. In focus groups, third year students were requested to give words which according to them have acquired new meanings on campus as compared to their common use anywhere else. Thus, such words should be believed to have their ‘campus’ meaning versus their ‘home’ meaning on the basis that their campus meanings might only be understood amongst university students while at the same time would be given a different meaning when used outside the university. Content analysis was done drawing on the underpinnings of communicative competence and componential theory of creativity frameworks. Data yielded significant patterns of language use including polysemy, among tertiary students; therefore, the study concludes that students’ exploitation of language is attributive of their communicative competence and creativity.